RFID-based conveyor belt for improve warehouse operations - Syafrial Fachri Pane; Rolly Maulana Awangga; Bayu Rahmad Azhari; Gilang Romadhanu Tartila (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The Government of the Republic of Indonesia is currently focusing on building logistics infrastructure to facilitate the distribution of logistics to all regions in Indonesia. The Distribution of logistics to each area requires an electronically connected warehouse so that information about goods in the warehouse can be monitored continuously. There are some problems with one of the logistics companies because the existing warehouse management technology is not sufficient enough, so the complex warehouse functions do not become dynamic. One of the solutions to solve the problem need to use RFID technology, conveyor belt, and robotic arm by using an Arduino microcontroller. This research uses Design Science Research Methodology which focuses on developing and improving the model performance of a system and using the prototyping model for system development. The test results state that the built system works well because it could lift, identify and sort goods by type. So, this research could answer the problem that happened at the warehouse.